(3HgLI GdfGXQjf hCfS GdYGQajfs - (3eMeO Hf YHO Gddg Hf eMeO, CHh YHO Gddg GdRehQj,J (B977 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Rjf PQjI fHjg eMeO Udi Gddg Ydjg hSde HJGL GdTQa hGdcQGeI CeG HYO , agPg fSNI GdTQa deMeOi gHJ YdjgG JhGaM GdHQcGJ GdeMeOjI , HQjGgG YHb fSjegG GdeYWGQ s
(3BNQgG (B:s
(3hGdLdhS eY GdCeQGA ajg BaJGf , GdJcHQ Ydi YHGO Gdgd hGdeOGgfI ai Ojf Gddg , hGdLdhS eY GdSagGA ajg BaJGf , ESJMGdI GdJgeI hESJMGdI GdMQeI , hGdLdhS eY GdUHjGf ajg BaJGf cKQg GdeRGL hGdfXQ Edi GdeQCI ZjQ EeQCJc PQjYI cd HdGA hTQ GfJgi HMeOs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HgGeTgG JUMjMGJ hebGHdGJ eY fSN CNQi hEKHGJ aQhbgGs
(3ai GdeYgO fSNI CNQi HQbe (B1437 (3JGQjN s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B239s
Keywords: (3GdJGQjNs